2011
DOI: 10.1021/ie1024276
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sensing Properties of CdS Nanoparticles Synthesized by Chemical Bath Deposition Method

Abstract: Thin films of CdS nanoparticles were synthesized by the chemical bath deposition (CBD) technique to investigate humidity response characteristics. The morphology and the crystal structure of CdS thin films were investigated by scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. The quartz crystal microbalance (QCM) technique was used to measure the water vapor adsorption and desorption rates of CdS thin films. The dynamic Langmuir model was used to analyze the kinetics of the moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 30 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…They found that the QCM resonance frequency changes linearly with varying relative humidity between 10 and 90%, which is directly related to mass uptake (the mass change (Δm) on the surface of the quartz crystal can be calculated using the Sauerbrey linear frequency change relationship 39 ). CdS nanoparticles studied here show similar behavior: the change in the frequency during the QCM measurements in our previous work 12 showed a linear relationship to relative humidity for RH values between 17 and 80%. However, it shows larger slope due to the condensation of water molecules at RH values above 80%.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 75%
See 3 more Smart Citations
“…They found that the QCM resonance frequency changes linearly with varying relative humidity between 10 and 90%, which is directly related to mass uptake (the mass change (Δm) on the surface of the quartz crystal can be calculated using the Sauerbrey linear frequency change relationship 39 ). CdS nanoparticles studied here show similar behavior: the change in the frequency during the QCM measurements in our previous work 12 showed a linear relationship to relative humidity for RH values between 17 and 80%. However, it shows larger slope due to the condensation of water molecules at RH values above 80%.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 75%
“…At low RH values, the large surface area of the first layer of the CdS nanoparticles with active OH groups will be filled with water molecules, which can be explained using the Langmuir model. 12 However, the resistance change shows a nonlinear (decreasing exponential) behavior as a function of increasing RH as a result of the possible condensation at higher relative humidity levels above 60%. On the other hand, the adsorption of water vapor on the CdS nanostructured surface is governed by a multilayer adsorption process, such that at higher RH values the decreasing rate in the resistance of the CdS nanoparticle sensing element can be explained by considering the increase in the ionic conduction mechanism of hydroxyl groups due to the decomposition of adsorbed water molecules under the influence of a relatively high electric field (close to 1 kV/cm) under various relative humidity conditions between 17 and 85% RH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Langmuir adsorption isotherm model has been frequently used 23,[34][35][36][37] for various gases such as humidity on organic or inorganic films to describe adsorption kinetics. According to this model, the rate of surface reaction to form a monolayer on the surface is given using the following equations:…”
Section: Sensing Properties Of Metal Oxide Nanofibersmentioning
confidence: 99%